A thermodynamical study on the complex formation of Cm(III) with methacrylate. (May 2018) - Fröhlich, Daniel R.; Panak, Petra J.
Abstract: Time-resolved laser fluorescence spectroscopy (TRLFS) is used to investigate the complexation of Cm(III) with methacrylate in NaCl solution as a function of the temperature (20–60 °C), ionic strength (0–2.5 mol/kg) and ligand concentration (0–0.2 mol/kg). The aqueous speciation of Cm(III) is obtained by deconvolution of the experimental emission spectra using pure component spectra of all Cm(III) species involved under the given experimental conditions. By applying the specific ion interaction theory (SIT), the temperature-dependent thermodynamic stability constants (log K 0 n (T), n = 1, 2) are determined by extrapolating the conditional stability constants to zero ionic strength. Additionally, the binary ion interaction coefficients (ε(i, j)) for the interaction between Cl − and the complex species [Cm(Meth)n ] 3−n (n = 1, 2) are calculated. The temperature dependency of log K 0 n in combination with the integrated Van't Hoff equation provides the molal standard reaction enthalpies and entropies (Δr H 0 m, Δr S 0 m ) of the respective complexation reactions confirming that both, the formation of [CmMeth] 2+ and [Cm(Meth)2 ] + are endothermic and entropy driven. At temperatures ≥70 °C, an additional Cm(III) species is formed that is attributed to the thermically induced polymerization of methacrylate. Highlights: Cm(III) complexation with methacrylate is investigated at T = 20–60 °C. The impact of methacrylate on Cm(III) speciation increases with increasing temperature. The complexation reactions of Cm(III) with methacrylate are endothermic/entropy driven.